Business Plan for Micro, Small and Medium Enterprises - Lisbet Eunice Pérez Anzardo; Irina Reyes Martínez; Ricardo Walfrido Proenza Ventura; Ika Hartika (Rowter Journal, 2024)
We are currently going through a global economic crisis that leads to the search for new strategies to improve the economy of the different countries of the world for the benefit of local development, based on the implementation of decrees that have favored and made business management more flexible. Likewise, during 2021, the creation of new economic actors was approved in Cuba to boost small businesses based on a socioeconomic benefit for society. Hence, the purpose of this research was to design a business plan for micro, small and medium enterprises (MSMEs). The municipality of Calixto García was used as a sample for its application to contribute to the growth and prospective development of new forms of non-state management. Theoretical methods such as analysis-synthesis, historical-logical, induction-deduction were used; and empirical such as scientific observation, interviews, study of normative documents, among others. As a result, the foundations were laid for the theoretical and practical deepening of the research and a methodology for the development of the business plan for MSMEs is presented, which was implemented in the Mr. Galletano Sole Proprietorship. From the reflection made in this study and from the theoretical and practical contribution, the need for the business plan as a fundamental tool for the positioning of this form of non-state management is demonstrated, which shows its profitability and possibility of growth from both operating and financial leverage.